2022
DOI: 10.1177/08933189221090491
|View full text |Cite
|
Sign up to set email alerts
|

Storytelling Networks that Build Community Power: Urban Equity Advocacy From a Communication Infrastructure Lens

Abstract: Urban scholars suggest that communication can be key to equity advocacy and organizing for social justice in cities, but a gap exists in studies grounded in communication theory. This article theorizes everyday urban equity advocacy through communication infrastructure theory (CIT), an ecological framework grounded in the notion that communities are discursively constructed. Sourced from 34 semi-structured interviews in Chicago, this article examines how organizers from social change-focused organizations acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Equity advocacy is communicatively constructed as members collectively produce education, collaboration, and storytelling of equity (Villanueva, 2022). Prior communication research has demonstrated the power of storytelling and how storytelling can foster shared community identity and construct community resilience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Equity advocacy is communicatively constructed as members collectively produce education, collaboration, and storytelling of equity (Villanueva, 2022). Prior communication research has demonstrated the power of storytelling and how storytelling can foster shared community identity and construct community resilience.…”
Section: Discussionmentioning
confidence: 99%
“…Community members' participation is essential for collective action that may lead to social changes because it provides a necessary space where dialogue can happen (Ganesh et al, 2022). Equity advocacy is communicatively constructed as members collectively produce education, collaboration, and storytelling of equity (Villanueva, 2022). Prior communication research has demonstrated the power of storytelling and how storytelling can foster shared community identity and construct community resilience.…”
Section: Discussionmentioning
confidence: 99%